The Android-based Interactive Pop-Up Multimedia Development to Improve Environmental Literacy, Learning Autonomy, and Learning Outcomes (Universitas Negeri Semarang, 2022)
The innovation of this research developed the android-based pop-up multimedia that can help students use Android as an interactive learning medium during the learning process and interactive multimedia can be tested for feasibility. This research is an important step in providing innovation in the development of interactive pop-up multimedia based on Android and shaping changes in the form of increasing students' the environmental literacy, learning autonomy, and learning outcome of learners. The applied research type was Research & Development with the ADDIE method. The researchers promoted the research for the fifth graders of Public Primary School Sumber and MIM Tumpuk in the academic year 2021/2022. The technique for collecting data was an interview, test, questionnaire, and observation. The results showed that 1) the characteristics of the android-based pop-up interactive multimedia were the one-application packaging, the material about the water cycle, and the modest and understandable language; 2) the android-based pop-up interactive media practicability reached a percentage of 97.49% with a high criterion, 3) the android-based interactive pop-up multimedia reached a percentage of 99% with valid criterion, and 4) the android-based interactive pop-up multimedia effectiveness influenced the improvement of environmental literacy based on questionnaire data, learning autonomy based on the questionnaire and learning outcome based on test and classical accomplishment calculation with a percentage of 94%, the N-Gain score of 0.69 with moderate category. It can be concluded that the development of the android-based pop-up interactive multimedia was effective to improve the environmental literacy, learning autonomy, and learning outcome of learners.